THE RULING COMMUNIST PARTY OF VIETNAM IN THE CURRENT SITUATION - Tram, Nguyen Thi (American International Journal of Social Science Research, 2021)
The aim of this study is to learn about the ruling Communist Party of Vietnam in the current situation. The study shows that in terms of leading, the Communist Party of Vietnam has affirmed to be the decisive factor in all victories of the Vietnamese revolutions. This paper seeks to address the following questions: 1/ prove the achievements of Vietnam obtained since the Communist Party of Vietnam is in power; 2/ generalize the views and theories on the ruling party, the ruling Communist Party, and the ruling Communist Party of Vietnam; 3/ present the results and discussion on the ruling Communist Party of Vietnam in the current situation. For these purposes, a variety of methods are used including analysis and synthesis, deduction and induction, abstraction and generalization, logic, history, and comparison to come to the findings and recommendations of the study.